Front Cover: Palladium Nanoparticles Hardwired in Carbon Nanoreactors Enable Continually Increasing Electrocatalytic Activity During the Hydrogen Evolution Reaction (ChemSusChem 22/2021). Issue 22 (28th October 2021) - Aygün, Mehtap; Guillen‐Soler, Melanie; Vila‐Fungueiriño, Jose M.; Kurtoglu, Abdullah; Chamberlain, Thomas W.; Khlobystov, Andrei N.; del Carmen Gimenez‐Lopez, Maria
Abstract : The Front Cover shows the self‐improving electrochemical activity of palladium nanoparticles hardwired into a graphitic step‐edge for hydrogen production. More information can be found in the Full Paper by M. Aygün, M. Guillen‐Soler, et al .